Penyelesaian Hukum Terhadap Penyerobotan Hak Atas Tanah Waris Oleh Pihak Ketiga : (Studi Kasus Di Desa Bancaran Kecamatan Bangkalan Kabupaten Bangkalan) - Chusnia Chusnia; Diyan Ibaidah Ayogi; Muhammad Ichlasul Amal; Sumriyah Sumriyah (Lembaga Pengembangan Kinerja Dosen, 2024)
Indonesia is an archipelagic country which has different legal characteristics, namely community life in villages which is closely related to family ties, which does not rule out the possibility that problems will arise such as the problem of dividing inherited land which often causes disputes within the family. This journal discusses legal solutions to the infringement of inherited land rights by non-heirs. The author emphasizes that seizure of inherited land by non-heirs can cause disputes and conflicts, as well as impact personal interests. Empirical juridical research method, using a statutory approach. The aim of this research is to find out the regulations for the distribution of inherited land rights and to understand the legal consequences of encroachment on inherited land rights by third parties. The results of this research show that the division of inheritance rights over land is regulated by the inheritance law that applies in Indonesia, there are three systems of inheritance law, namely Customary Inheritance Law, Islamic Inheritance Law, and Civil Inheritance Law, and the regulation of the distribution of inheritance rights over inheritance that applies in Indonesia. The legal consequence of encroachment on inheritance rights by a third party is that the heirs receive compensation for material and immaterial losses resulting from unlawful acts calculated in the form of money or by replacing goods or objects that have been damaged or confiscated, according to the value of the goods.